2015
DOI: 10.1111/adb.12256
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol exposure decreases CB1receptor function at GABAergic synapses in the rat central amygdala

Abstract: The endogenous cannabinoids (eCBs) influence the acute response to ethanol and the development of tolerance, dependence and relapse. Chronic alcohol exposure alters eCB levels and type 1 cannabinoid receptor (CB 1 ) expression and function in brain regions associated with addiction. CB 1 inhibits GABA release, and GABAergic dysregulation in the central nucleus of the amygdala (CeA) is critical in the transition to alcohol dependence. We investigated possible disruptions in CB 1 signaling of rat CeA GABAergic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 67 publications
4
38
1
Order By: Relevance
“…After chronic alcohol exposure and protracted withdrawal, however, there may be an eCB/CB1 signaling deficiency, which could also increase alcohol intake via the negative reinforcement mechanism. This notion is supported by several findings: [1] there is down-regulation of CB1 expression and function observed during protracted alcohol withdrawal in rats [Mitrirattanakul et al, 2007;Varodayan et al, 2016]; [2] in human imaging studies, decreased CB1 availability is observed in heavy-drinking alcoholics that persists into abstinence [Hirvonen et al, 2013;Ceccarini et al, 2014]; and [3] a lowered plasma AEA level is found in alcohol dependent patients during recent abstinence [Mangieri et al, 2009]. …”
Section: Endocannabinoid Systemmentioning
confidence: 70%
“…After chronic alcohol exposure and protracted withdrawal, however, there may be an eCB/CB1 signaling deficiency, which could also increase alcohol intake via the negative reinforcement mechanism. This notion is supported by several findings: [1] there is down-regulation of CB1 expression and function observed during protracted alcohol withdrawal in rats [Mitrirattanakul et al, 2007;Varodayan et al, 2016]; [2] in human imaging studies, decreased CB1 availability is observed in heavy-drinking alcoholics that persists into abstinence [Hirvonen et al, 2013;Ceccarini et al, 2014]; and [3] a lowered plasma AEA level is found in alcohol dependent patients during recent abstinence [Mangieri et al, 2009]. …”
Section: Endocannabinoid Systemmentioning
confidence: 70%
“…Thus, relatively small reductions in CB1 expression at glutamatergic terminals might have a much more dramatic impact on receptor function relative to GABAergic terminals which express relatively high levels of the receptor. A more prolonged CIE exposure may be potentially required before reductions in GABAergic CB1 expression sufficient to impair CB1 function of this terminal population occur [60]. …”
Section: 0 Discussionmentioning
confidence: 99%
“…Rats were anesthetized (3–5% isoflurane) and decapitated, and the brains placed in oxygenated (95% O 2 /5% CO 2 ), cold high-sucrose solution (pH 7.3–7.4; in mM): 206.0 sucrose; 2.5 KCl; 0.5 CaCl 2 ; 7.0 MgCl 2 ; 1.2 NaH 2 PO 4 ; 26.0 NaHCO 3 ; 5.0 glucose; 5.0 HEPES, as previously described (Herman et al, 2013; Herman and Roberto, 2016; Roberto et al, 2010b; Varodayan et al, 2016). The brains were coronally sliced (300 μm) and the tissue incubated (30 min at 37 °C, then 30 min at room temperature) in oxygenated artificial cerebrospinal fluid (aCSF; in mM): 130.0 NaCl; 3.5 KCl; 2 CaCl 2 ; 1.25 NaH 2 PO 4 ; 1.5 MgSO 4 ; 24 NaHCO 3 ; 10 glucose.…”
Section: Methodsmentioning
confidence: 99%